Inovasi dan Kreativitas, Kunci dari Kesuksesan Kewirausahaan - Haribowo, Siget Fitrianto; Wibowo, IG. Jarot Febri Setyo; Rahayu, Wening Patmi; Winarno, Agung (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
The crucial role that creativity and innovation play in fostering entrepreneurial success is examined in this study. Entrepreneurs must not only stay relevant but also promote sustainable growth in a fiercely competitive and quickly evolving business environment. Creativity and innovation are essential components that set successful companies apart from those that find it difficult to adjust. Despite their significance, little is known about the direct effects of these two ideas on entrepreneurial outcomes, especially for small and medium-sized businesses (SMEs). The goal of this essay is to present a thorough examination of the elements that affect creativity and innovation in entrepreneurship, looking at how they interact and how they affect long-term company performance. The study also identifies the obstacles that prevent inventive and creative processes in business endeavors and provides actionable suggestions for entrepreneurs to improve these areas of their operations. This study aids in the creation of fresh theoretical frameworks and useful methods for entrepreneurship by pinpointing the primary forces behind creativity and innovation. The results highlight how important it is to develop a creative and inventive attitude since it is necessary to get a competitive edge and maintain long-term company success in the fast-paced global market of today.